Strongly bound excitons in anatase TiO2 single crystals and nanoparticles - E. Baldini (Nature Portfolio, 2017)
Here the authors combine steady-state angle-resolved photoemission spectroscopy, ellipsometry and ultrafast two-dimensional ultraviolet spectroscopy to examine the role of many-body correlations in anatase TiO2, revealing the existence of strongly bound excitons in single crystals and nanoparticles.